Didactic Design Research in Overcoming Epistemological Barriers in Mathematics Learning; A Systematic Literature Review - Erin Clariza Br Surbakti; Emi Pujiastuti (Journal of Creativity Student, 2026)
Epistemological obstacles are among the primary factors that impede students' understanding of mathematical concepts. Didactical Design Research (DDR) emerges as a learning-obstacle-based approach that offers a systematic framework for identifying and addressing these barriers. However, comprehensive reviews mapping DDR research trends in the context of epistemological obstacles in mathematics education remain limited. This study aims to: (1) analyze trends in DDR research on epistemological obstacles, (2) identify the most prevalent types of epistemological obstacles, (3) map the didactic design strategies employed, and (4) assess the effectiveness of DDR implementation. A Systematic Literature Review (SLR) following the PRISMA protocol was conducted. Articles were retrieved from Google Scholar, ERIC, and Sinta databases covering 2015–2025. After rigorous selection, 27 articles met the inclusion criteria. Findings indicate that: (1) DDR research has grown significantly from 2020 to 2025, particularly at the junior and senior secondary levels; (2) dominant epistemological obstacles involve difficulties in abstract concept comprehension, symbolic misconceptions, and failure to transfer concepts; (3) effective didactic strategies include mathematical visualization, contextual scaffolding, reflective discussion, and structured cognitive conflict; and (4) consistent DDR implementation demonstrably improves students’ conceptual understanding. These findings carry strategic implications for developing adaptive, obstacle-informed mathematics learning designs.